New criteria of resectability for pancreatic cancer: A position paper by the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery (JSHBPS). (20th October 2021) - Oba, Atsushi; Del Chiaro, Marco; Satoi, Sohei; Kim, Sun‐Whe; Takahashi, Hidenori; Yu, Jun; Hioki, Masayoshi; Tanaka, Masayuki; Kato, Yoshiyasu; Ariake, Kyohei; Wu, Y.H. Andrew; Inoue, Yosuke; et al.
Abstract: The symposium "New criteria of resectability for pancreatic cancer" was held during the 33nd meeting of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery (JSHBPS) in 2021 to discuss the potential modifications that could be made in the current resectability classification. The meeting focused on setting the foundation for developing a new prognosis‐based resectability classification that is based on the tumor biology and the response to neoadjuvant treatment (NAT). The symposium included selected experts from Western and Eastern high‐volume centers who have discussed their concept of resectability status through published literature. During the symposium, presenters reported new resectability classifications from their respective institutions based on tumor biology, conditional status, pathology, and genetics, in addition to anatomical tumor involvement. Interestingly, experts from all the centers reached the agreement that anatomy alone is insufficient to define resectability in the current era of effective NAT. On behalf of the JSHBPS, we would like to summarize the content of the conference in this position paper. We also invite global experts as internal reviewers of this paper for intercontinental cooperation in creating an up‐to‐date, prognosis‐based resectability classification that reflects the trends of contemporary clinical practice. Abstract : On behalf of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery, Oba et al. report on new criteria of resectability for pancreatic cancer. Global experts were invited as internal reviewers for intercontinental cooperation in creating an up‐to‐date prognosis‐based resectability classification that reflects the trends of contemporary clinical practice with effective neoadjuvant treatment.